Isolation of C4-synthesizing cells from guinea-pig liver by Ficoll density gradient centrifugation - Ilgen, Christine Littleton (1974)
Cells which synthesize the fourth component of complement have been isolated from guinea-pig liver through rate zonal density gradient centrifugation of suspensions of liver cells on continuous density gradients (2 to 15 per cent) of Ficoll. This procedure separates non-parenchymal cells from parenchymal cells on the basis of size. Cells which synthesized C4 were identified as low density, non-parenchymal cells which comprised only a small proportion of the cells added to the gradient. Phagocytic cells were restricted to the same portion of the gradient as cells which synthesized C4, and there is evidence that cells which synthesize C4 are also phagocytic.